(untitled) (Iranian Journal of Kidney Diseases, 2018)
Introduction. Kidney transplantation is considered the ideal treatment for end-stage renal disease. Acute rejection can influence graft survival. The aim of this study was to propose a classification system for acute rejection based on factor analysis. Materials and Methods. Data were collected from kidney transplant recipients with acute rejection diagnosis based on standard histological variables, the presence of peritubular eosinophils, and immunolabeling for lysozyme and myeloperoxidase in kidney tissue. Factor analysis was employed for data reduction and generation of a new case classification, with orthogonal rotation as a strategy to simplify factors, and principal component analysis was used as an extraction method. Results. Seventy-nine kidney biopsies were obtained from 74 patients. The total population was divided into humoral rejection (39.2%), cellular rejection (34.1%), and mixed acute rejection (26.7%). No significant differences were found between the three groups in clinical and biochemical variables. We extracted 4 factors using factor analysis. The 1st factor was characterized by the presence of capillaritis, plasma cells infiltration, tubulitis, and inflammation. The 2nd factor included positivity for lysozyme and myeloperoxidase, while the 3rd factor included the presence of eosinophils and glomerulitis. The 4th component consisted of the presence of C4d and endarteritis. The cases belonging to the 3rd factor showed the greatest increase in serum creatinine. The cases belonging to the 4th factor exhibited greater urinary excretion of proteins. Conclusions. This proposal of classification of acute rejection could contribute to evaluate the prognosis of kidney transplant recipients.